If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 7 = 43 Reorder the terms: 7 + 3m = 43 Solving 7 + 3m = 43 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3m = 43 + -7 Combine like terms: 7 + -7 = 0 0 + 3m = 43 + -7 3m = 43 + -7 Combine like terms: 43 + -7 = 36 3m = 36 Divide each side by '3'. m = 12 Simplifying m = 12
| 6(2+c)=5(c-5) | | 17=-1.85t^2+20t+1 | | 8(4c-1)-2=30c+8 | | 8(y-1)=4y-28 | | 6n+17=18n-5 | | 5-4x=13+4x | | -4y-11=6y+29 | | 5(6x-2)=31x | | 7c+2=-19 | | 4z=60z+3 | | 4z=60z+60 | | 7x-3x-10=4x | | 6x^3-20x^3=0 | | (4w-9)(2-w)=0 | | 3y+24=6y-3 | | -3=-8x | | (x+3)(x+2)=2 | | 4(3c-1)-3=7c+8 | | 17x+5y=29 | | 2x^2=19x-24 | | 11x^2+55x+19x+95=x^2+6x+5 | | z^2-z+20=0 | | x(x-7)+10=0 | | 21=y-14 | | 3p+9=5p-7 | | x^2=115 | | 60+3y-5=-4y+42+9 | | 10x+3y-5=-4y+7x+9 | | 3x+9=17+2x | | 9s^2+12s+4= | | 4x^2-15x+39=9x+4 | | 8x+2=7-2x |